Al-Ghazali in the Political Ethics and Governance: An Analytical Studies on Al-Tibbr al-Masbūk fī Naṣīḥah al-Mulk - Muhammad Yaufi Nur Mutiullah (Tasfiyah: Jurnal Pemikiran Islam, 2023)
This article discusses Imam Al-Ghazali’s views on political ethics and governance. This type of research is literature using analytical methods. The primary source used by researchers is one of Imam Al-Ghazali’s works, namely “Al-Tibbr al-Masbūk fī Naṣīḥah al-Mulk” and several other relevant works. This article answers the problem when in the 16th century, there was a separation between ethics and politics in the West which was pioneered by an Italian statesman named Niccolo Machiavelli which resulted in that the mindset of the government was based on its acceptance of the political system of its time. This discussion becomes important as a response to debates and dialectics about the importance of ethics in politics. This study concludes that Al-Ghazali proposed that the government system be made up of a board of directors in carrying out every government program in order to create productivity and effectiveness in running the government. The Diwan should have three institutions in the country: the deliberative council, the judiciary and the ministerial body. In addition, ethics needs to be included in the political system, this is a critique of scholars who reject ethical participation in politics. Al-Ghazali advised the rulers about the importance of ethics in politics and government. It is formulated in seven principles namely fairness, competence, humility, honesty, responsiveness, sincerity, and gentleness.